2019
DOI: 10.1186/s43008-019-0012-8
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomics as a tool to identify fungal species and subspecies in mixed communities – a proof of concept under laboratory conditions

Abstract: High-throughput sequencing (HTS) enables the generation of large amounts of genome sequence data at a reasonable cost. Organisms in mixed microbial communities can now be sequenced and identified in a culture-independent way, usually using amplicon sequencing of a DNA barcode. Bulk RNA-seq (metatranscriptomics) has several advantages over DNA-based amplicon sequencing: it is less susceptible to amplification biases, it captures only living organisms, and it enables a larger set of genes to be used for taxonomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Metatranscriptomic analysis of this interaction model demonstrated genes encoding the transcription of 1,2-bis(4-hydroxyphenyl)-2-propanol (1-BP) into 4-hydroxybenzaldehyde (4-HBD) and 4-hydroxy-acetophenone (4-HAP) via 3,4-dihydroxybenzoate (3,4-DHB) and 3-oxoadipate (3-ODP), respectively, to the tricarboxylic acid cycle (TCA)cycle. Marcelino et al ( 2019 ) identified fungal species and subspecies in a mixed community by using metatranscriptomics. This study suggested a strain-level discrepancy between the Cryptococcus fungal species and their in-situ mock communities.…”
Section: Recent Advanced Technologies Employed In Bioremediation For mentioning
confidence: 99%
“…Metatranscriptomic analysis of this interaction model demonstrated genes encoding the transcription of 1,2-bis(4-hydroxyphenyl)-2-propanol (1-BP) into 4-hydroxybenzaldehyde (4-HBD) and 4-hydroxy-acetophenone (4-HAP) via 3,4-dihydroxybenzoate (3,4-DHB) and 3-oxoadipate (3-ODP), respectively, to the tricarboxylic acid cycle (TCA)cycle. Marcelino et al ( 2019 ) identified fungal species and subspecies in a mixed community by using metatranscriptomics. This study suggested a strain-level discrepancy between the Cryptococcus fungal species and their in-situ mock communities.…”
Section: Recent Advanced Technologies Employed In Bioremediation For mentioning
confidence: 99%
“…We validated the CCMetagen pipeline with a fungal community previously generated in vitro by culturing, processing, and sequencing 15 fungal species ( [34], Additional file 5). The analyses were performed using the NCBI nt collection as a reference.…”
Section: Biological Data Set 1: Experimentally Seeded Fungal Metatranmentioning
confidence: 99%
“…We validated the CCMetagen pipeline using two biological data sets: one defined fungal community (biological data set 1) and one set of environmental samples (biological data set 2). The fungal community was constructed by culturing, pooling, and sequencing the same 15 fungal species used in the metatranscriptome simulated in silico (SRA Bio-Project number PRJNA521097) [34].…”
Section: Ccmetagen Applied To Real Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rst SARS-CoV-2 complete genome sequence, Wuhan-Hu-1 (MN908947), was derived from RNA extracted directly from the patient's bronchoalveolar lavage uid using the whole genome meta-transcriptomics approach [4]. This unbiased sequencing approach allows culture-free detection of novel [4] or known pathogens [9]. The metatranscriptomics approach, however, is not always able to produce the entire genome sequence due in part to the presence of host RNAs that contribute to the majority of the generated sequencing reads [4].…”
Section: Introductionmentioning
confidence: 99%